Annotated checklist and distribution of the lizards of Iran - Šmíd, Jiří; Moravec, Jiří; Kodym, Petr; Kratochvíl, Lukáš; Yousefkhani, Seyyed Saeed Hosseinian; Frynta, Daniel (Zootaxa, 2014)
We present a comprehensive summary of the distribution of the lizards of Iran accompanied by an annotated checklist. The updated maps of distribution of all 146 species of 41 genera of 11 families are based on all available bibliographic records, catalogues of museum collections and our own field observations. The final dataset used for the distribution maps contains 8525 georeferenced records and cover 41% of the country when plotted on a grid of 0.25° × 0.25° resolution. The dataset is publicly accessible through GBIF portal (http://www.gbif.org/dataset/7db4f705-61ae-4c6e-9de2-06674e7d46b2). Following the latest biogeographic division of the country, 53% of the species (76 species) inhabit the Iranian Province, 41% (60 species) the Western Asian mountain transition zone, 9% (13 species) the Turanian Province, and 18% (27 species) the Arabian Province. In addition, 2% (3 species) reach Iran from the Indo-Malay biogeographic region and 2% (3 species) are believed to have been introduced to Iran by humans. Endemic species (46) represent 32% of the known species diversity. The most species-rich family of lizards in Iran is Lacertidae with 47 species, followed by Gekkonidae (41), Agamidae (18), Scincidae (15), Phyllodactylidae (10), Sphaerodactylidae (4), Eublepharidae and Uromastycidae (3), Anguidae and Varanidae (2), and Trogonophidae with one representative.